The complete guide to gazebos and arbors - Schmidt, Philip; Black & Decker Corporation (Towson, Md.) (Chanhassen, Minn. : Creative Pub. Internatiional, 2007)
"Shows basic techniques for building sheltering structures in the landscape, and provides project plans and directions for more than 12 versatile, flexible architectural projects"--Provided by publisher.
Includes index.
At head of title: Black & Decker.
Keywords: Gazebos; Arbors